Biomodulator of Diode Laser Irradiation on Odontoblast-Like Cells by Expression of Vascular Endothelial Growth Factor-A and Transforming Growth Factor-β1 - Devi Eka Juniarti, - (2022)
Objective This study aimed to prove that the effect of diode laser 650-nm irradiation to the expression of vascular endothelial growth factor (VEGF)-A and transforming growth factor (TGF)-β1 plays important roles in dental pulp-regulating cell proliferation, differentiation, and revascularization. Materials and Methods The research was performed by randomized posttest only control group design using Rattus norvegicus. A total of 48 samples were provided and divided into eight groups of 6 samples each with a random-sample allocation. Each group were prepared, and perforation of maxillary first molar were done. In control groups (groups 1–4), glass ionomer cement (GIC) was used to restore the teeth, while in laser groups (groups 5–8), the teeth were irradiated with diode laser 650 nm for 40 seconds before application of GIC. Half of the groups (groups 1, 2, 5, and 6) were necropsied in 7 days, and the rest (groups 3, 4, 7, and 8) were necropsied in 14 days. Immunohistochemistry (IHC) evaluation were implemented to check the expression of both VEGF-A and TGF-β1. Statistical Analysis Both data of VEGF-A and TGF-β1 expression were analyzed using a one-way ANOVA (α ¼ 0.05) with SPSS statistical software. Results The study showed that the diode laser 650-nm irradiation increased expression of VEGF-A and TGF-β1, and there was a significant difference between diode laser and control group on VEGF-A expression (p¼ 0.001) and TGF- β1 (p ¼ 0.000) on days 7 and 14. Conclusion Diode laser 650 nm with 40-second irradiation time shows increment from day 7 to day 14 reflecting increase in pulp healing by modulating VEGF-A and TGF- β1 expression since days 7 to 14.